Electrochemical behavior of the flower shaped CoMn2O4 spinel structure assembled for effective HER from water splitting. (20th May 2021) - Lee, Junhee; Son, Namgyu; Park, No-Kuk; Ryu, Ho-Jung; Baek, Jeom-In; Sohn, Youngku; Do, Jeong Yeon; Kang, Misook
Highlights: A flower sheet typed CoMn2 O4 /NNF with distorted spinel structure. The CoMn2 O4 /NNF electrode with excellent durability and long-term stability. Improvement of HER activity on CoMn2 O4 by higher electrochemically active surface area. The promoted Volmer step on (101) crystal plane of CoMn2 O4 . Abstract: This research focuses on the electrochemical properties of the spinel structure, which is a specific structure of Co-Mn bimetal, and the active species therein, rather than the hydrogen evolution (HER) performance of Co-Mn-based bimetal oxides. The catalysts of four types are prepared by following a solvothermal process and coated on a NiOOH/NF support electrode (NNF). Compared to the CoO and Mn2 O3 single particle-assembled electrodes, the CoMn2 O4 /NNF electrode coated with the flower shaped CoMn2 O4 bimetallic particle displays the higher stability in HER. The double-layer capacitance of the CoMn2 O4 /NNF electrode (25.6 mF cm −2 ) is approximately three or four times higher than those of the CoO/NNF and Mn2 O3 /NNF electrodes, meaning that the CoMn2 O4 /NNF electrode has a larger electrochemical active surface area. The CoMn2 O4 /NNF electrode additionally has a low overpotential (132 mV), implying that it's HER activity is superior to the other electrocatalysts. It is demonstrated that the structural characteristic of CoMn2 O4 contributes to the excellent stability in a long-term HER test. The Density-functional theory (DFT) calculations reveal that the Volmer step is promoted on the (101) crystal plane of CoMn2 O4 ; i.e., the rate of H* formation increases, which causes the HER kinetics to be enhanced. Thus, the experimental and theoretical findings in this study prove the excellent HER performance of CoMn2 O4 particles. Graphical abstract: Image, graphical abstract